Anti‐eosinophil activity and clinical efficacy of the CRTH2 antagonist OC000459 in eosinophilic esophagitis. Issue 3 (5th February 2013) - Straumann, A.; Hoesli, S.; Bussmann, Ch.; Stuck, M.; Perkins, M.; Collins, L. P.; Payton, M.; Pettipher, R.; Hunter, M.; Steiner, J.; Simon, H.‐U.
Abstract Background Eosinophilic esophagitis (EoE) is a chronic, Th2‐type inflammatory disease. Chemoattractant receptor‐homologous molecule on Th2 cells (CRTH2) is a prostaglandin D2 (PGD2) receptor, expressed by Th2 cells and other inflammatory cells, including eosinophils and basophils, that mediates chemotaxis and activation. OC000459 is a selective CRTH2 antagonist and would be expected to suppress eosinophilic tissue inflammation. The purpose of this study was to evaluate the efficacy and safety of an OC000459 monotherapy in adult patients with active, corticosteroid‐dependent or corticosteroid‐refractory EoE. Methods In this randomized, double‐blind, placebo‐controlled trial, 26 adult patients (m/f = 22/4; mean age 41 years, range 22–69 years) with active EoE, dependent or resistant to corticosteroids, were treated either with 100 mg OC000459 (n = 14) or placebo (n = 12) twice daily. Pre‐ and post‐treatment disease activity was assessed clinically, endoscopically, histologically, and via biomarkers. The primary end point was the reduction in esophageal eosinophil infiltration. Results After an 8‐week OC000459 treatment, the esophageal eosinophil load decreased significantly, from 114.83 to 73.26 eosinophils per high‐power field [(eos/hpf), P = 0.0256], whereas no reduction was observed with placebo (102.80–99.47 eos/hpf, P = 0.870). With OC000459, the physician's global assessment of disease activity improved from 7.13 to 5.18 (P = 0.035). OC000459 likewise reduced extracellular deposits of eosinophil peroxidase and tenascin C, the effects not seen with placebo. No serious adverse events were observed. Conclusions An 8‐week treatment with the CRTH2‐antagonist, OC000459, exerts modest, but significant, anti‐eosinophil and beneficial clinical effects in adult patients with active, corticosteroid‐dependent or corticosteroid‐refractory EoE and is well tolerated.